MESIN PENYERUT BAMBU SOLUSI TEPAT MENINGKATKAN PENDAPATAN PENGRAJIN SANGKAR BURUNG TANPA LISTRIK - S, Siswanto; Prananta, Jevry Dwi; Puruhita, Ardiyah Purna; Mujahidin, Moh. (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Bamboo is a material grating bird cage, bird cage measuring 50 cmÂ² requires Â± 300 bars. The high price of machine, operating costs and electricity rates make craftsmen using the manual method, so that the impact on economic income families. Observation, and Prototype Test is the method used to determine the actual condition, determine the slicing mechanism and reduce errors. Machine dimensions 400 mm 1500x500x1000 mm flywheel, 8 roll, 2 pieces knife capable of slicing 1 to 3 bars of bamboo bird cage in a single process can increase the capacity of the bird cage bars 3 times manually.